Pengaruh Harga dan Fasilitas Terhadap Keputusan Berkunjung di Jasmine Park Cisauk, Tangerang Selatan, Provinsi Banten - Freddy Triono; Fetty Asmaniati; Ismeth Emier Osman; Novita Widyastuti Sugeng; Agus Riyadi (Journal of Hospitality Accommodation Management (JHAM), 2025)
This study aims to analyze the impact of price and facilities on visitors' decision to visit Jasmine Park Cisauk. The approach used is quantitative with a descriptive design, and data was collected using accidental sampling from 105 respondents who are visitors of Jasmine Park. The research instrument used a five-point Likert scale questionnaire to measure the respondents' perceptions of price, facilities, and visit decisions. Data were analyzed using multiple linear regression through the SmartPLS application. The results indicate that price and facilities significantly affect the decision to visit. Affordable prices that match the quality of the facilities offered can attract visitors. In contrast, complete and comfortable facilities such as a mini zoo, thematic gardens, and adequate parking areas enhance visitors' positive experience and satisfaction. This study concludes that price and facilities are important factors influencing the decision to visit Jasmine Park. Suggestions for the management include maintaining the quality of facilities and increasing the diversification of tourist attractions. The local government is recommended to support infrastructure development and promote tourism destinations. Visitors are expected to maintain cleanliness and preserve nature around the tourist area.